(untitled) (Knjiženstvo, journal for studies in literature, gender and culture, 2023)
The purpose of this paper is to establish the differences between the male and female variants of Bildungsroman, as well as to follow the development of the female ones, from its beginning to the 20th century. As a result of great historical, social and cultural changes in society, as well as of the modernist movement, this kind of novel experienced significant changes. Women novelists became even more aware of their awakening to limitations, which are still determined by a patriarchal society.